The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1515/hfsg.1991.45.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Increased Extractability of Irradiated Wood Meal

Abstract: Black poplar wood meal was irradiated with gamma-rays and subsequcntly activated with 17.5% NaOH and fractionated with ethanol, wate r, and 5% NaOH solution. Irradiation with a dose of 100 M r ad incrcased the extractability from 16.5% to 32.5% of the starting matcrial. Whcn the matcrial was extracted with water, accton, and 5% NaOH without activation with 17.5% NaOH, 60.4% of the lignoceltulose material was isolated and the rcsidue representcd only 5.9%. Whcn the matcrial was extracted in oneStep with 5% NaOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A strong linear correlation was found between gamma radiation doses (G) and dm (Despot et al, 2007;Figure 6). www.intechopen.com chains and the solubility of smaller cellulose fragments in water (Seifert, 1964;Tabirih et al, 1977;Šimkovic et al, 1991). Despot et al (2007) reported that for 10 days after gamma treatment dm was significantly higher than after 150 days for each applied dose (Table 2).…”
Section: Decrease In Mass By Leaching (Dm)mentioning
confidence: 98%
See 1 more Smart Citation
“…A strong linear correlation was found between gamma radiation doses (G) and dm (Despot et al, 2007;Figure 6). www.intechopen.com chains and the solubility of smaller cellulose fragments in water (Seifert, 1964;Tabirih et al, 1977;Šimkovic et al, 1991). Despot et al (2007) reported that for 10 days after gamma treatment dm was significantly higher than after 150 days for each applied dose (Table 2).…”
Section: Decrease In Mass By Leaching (Dm)mentioning
confidence: 98%
“…These changes should mostly influence the hygroscopicity (Fengel and Wegener, 1989) and tension strength of gamma-irradiated wood, because it becomes more brittle (Divos and Bejo, 2005). Furthermore, gamma irradiated wood is more susceptible to chemical and enzymatic degradation (Seifert, 1964;Klimentov and Bysotskaia, 1979;Klimentov et al, 1981;Ardica et al, 1984;Šimkovic et al, 1991;Magaudda et al, 2001;Struszczyk et al, 2004;Despot et al, 2006;Hasan, 2006 andHasan et al, 2006a;.…”
Section: Total Amount Of Water-soluble Carbohydrates (Tsc)mentioning
confidence: 99%
“…Gamma-irradiated wood is more susceptible to chemical and enzymatic degradation (Seifert 1964;Klimentov and Bysotskaia 1979;Klimentov et al 1981;Ardica et al 1984;Š imkovic et al 1991;Magaudda et al 2001;Struszczyk et al 2004;Despot et al 2006). …”
Section: Introductionmentioning
confidence: 99%